Systemic Inflammation Increases the Susceptibility to Levodopa-Induced Dyskinesia in 6-OHDA Lesioned Rats by Targeting the NR2B-Medicated PKC/MEK/ERK Pathway - Yan, Aijuan; Song, Lu; Zhang, Yu; Wang, Xijin; Liu, Zhenguo (Frontiers in Aging Neuroscience, 2021)
Background: The long-term administration of levodopa (L-dopa), the gold-standard treatment for Parkinson's disease (PD), is irreparably associated with L-dopa-induced dyskinesia (LID), which dramatically affects the quality of life of patients. However, the underlying molecular mechanisms of how LID exacerbates remain unknown. Neuroinflammation in the striatum plays an active role in LID. These findings prompt an investigation of non-neuronal mechanisms of LID. This study will examine the effects of systemic inflammation in the development and progression of LID. Methods: To evaluate the possible influence of systemic inflammation in the appearance of LID, the PD rats received an intraperitoneal (IP) injection of various concentrations of lipopolysaccharides (LPS, 1, 2, and 5 mg/kg) or saline. One day later, these PD rats started to receive daily treatment with L-dopa (6 mg/kg) along with benserazide (6 mg/kg) or saline for 21 days, and dyskinesia was evaluated at several time points. Moreover, the activation of microglia and astrocytes and the molecular changes in NR2B and mGLUR5 signaling pathways were measured. Results: We found that systemic inflammatory stimulation with LPS exacerbated the intensity of abnormal involuntary movements (AIMs) induced by L-dopa treatment in 6-hydroxydopamine (6-OHDA) lesioned rats. The LPS injection activated the gliocytes and increased the levels of proinflammatory cytokines in the striatum in LID rats. The PD rats that received the LPS injection showed the overexpression of p-NR2B and NR2B, as well as activated PKC/MEK/ERK and NF-κB signal pathways in response to the L-dopa administration. On the contrary, clodronate-encapsulated liposomes (Clo-lipo), which could suppress the inflammatory response induced by peripheral LPS injection, improved behavioral dysfunction, inhibited neuroinflammation, prevented NR2B overexpression, and decreased the phosphorylation of PKC/MEK/ERK and NF-κB signaling pathways. Conclusion: This study suggests that systemic inflammation, by exacerbating preexisting neuroinflammation and facilitating NR2B subunit activity, may play a crucial role in the development of LID. The administration of Clo-lipo restores the effects of LPS and decreases the susceptibility to LID in 6-OHDA lesioned rats.